1992
DOI: 10.1073/pnas.89.3.1138
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expression of human adenosine deaminase in vascular smooth muscle cells of rats: a model for gene therapy.

Abstract: Gene transfer into vascular smooth muscle cells in animals was examined by using recombinant retroviral vectors containing an Escherichia coli beta-galactosidase gene or a human adenosine deaminase (adenosine aminohydrolase, EC 3.5.4.4) gene. Direct gene transfer by infusion of virus into rat carotid arteries was not observed. However, gene transfer by infection of smooth muscle cells in culture and seeding of the transduced cells onto arteries that had been denuded of endothelial cells was successful. Potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(47 citation statements)
references
References 25 publications
(15 reference statements)
1
45
0
1
Order By: Relevance
“…4 When the target cell type for the ADA vector is skin fibroblasts gene expression is shut down, however, the same vector maintains high levels of expression in vascular endothelial cells. 5 Several vector designs expressing the lysosomal enzyme ␤-glucuronidase (GUSB) are down-regulated in most cells, but consistently maintain expression in a small subset (1-5%) in both fibroblasts and hematopoietic cells. [6][7][8][9][10][11][12] The presence of the selectable marker sequence, bacterial neomycin resistance gene (neo), has produced inconsistent effects on retroviral vector expression.…”
Section: Introductionmentioning
confidence: 99%
“…4 When the target cell type for the ADA vector is skin fibroblasts gene expression is shut down, however, the same vector maintains high levels of expression in vascular endothelial cells. 5 Several vector designs expressing the lysosomal enzyme ␤-glucuronidase (GUSB) are down-regulated in most cells, but consistently maintain expression in a small subset (1-5%) in both fibroblasts and hematopoietic cells. [6][7][8][9][10][11][12] The presence of the selectable marker sequence, bacterial neomycin resistance gene (neo), has produced inconsistent effects on retroviral vector expression.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that this cell-seeding technique gives long-term and biologically significant gene expression in the intima. 10 In the present study, we demonstrate that increased PAI-1 expression in the rat carotid artery inhibits neointimal formation, increases platelet accumulation, and accelerates endothelialization of the injured carotid artery. Our findings demonstrate that PAI-1 plays an important role in neointimal formation in the rat and suggests that PAI-1 may influence the biology of the atherosclerotic lesion in humans.…”
mentioning
confidence: 74%
“…Transduced SMCs were seeded onto the luminal surface as previously described. 10 SMCs (10 5 ) were infused into the carotid artery and allowed to attach for 10 minutes.…”
Section: Smc Seeding In Vivomentioning
confidence: 99%
“…There have been various cell types which have been studied for their potential usefulness in gene therapy, including epithelial cells, endothelial cells, skin fibroblasts and myoblasts, but each of these cell lines has had problems with viability, secretion, long-term culture or rejection. 1,3,[7][8][9][10] The use of endothelial YS cells in gene therapy offers several advantages over currently used systems. These cells have a long lifespan even after being grafted in animals, they retain their phenotype over an extended period of time, they are good secretors of exogenous foreign proteins, and they are not tumorigenic when grafted in immunocompromised animals.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The ultimate cell to be used for cell-based gene therapy has the requirements of being easily cultured, easily transfected with genetic material, able to secrete high levels of an exogenous protein, able to be transplanted in vivo, nonmalignant, and no observed host-versus-graft effects. Atherosclerotic cardiovascular disease is the leading cause of death in the Western world today.…”
Section: Introductionmentioning
confidence: 99%